The deathwatch beetle : a mystery - Eriksson, Kjell, 1953- (Eriksson, Kjell, 1953- Ann Lindell, 2021)
"Former Swedish police inspector Ann Lindell returns in internationally bestselling and award-winning Kjell Eriksson's newest mystery, The Deathwatch Beetle..."--